Dietary inclusion of anthocyanin-rich black cane silage treated with ferrous sulfate heptahydrate reduces oxidative stress and promotes tender meat production in goats - Purba, Rayudika Aprilia Patindra; Suong, Ngo Thi Minh; Paengkoum, Siwaporn; Schonewille, Jan Thomas; Paengkoum, Pramote (Frontiers in Veterinary Science, 2022)
Pre-treating anthocyanin-rich black cane with ferrous sulphate heptahydrate (FSH) produces high-quality silage with less anthocyanin and nutritional loss. However, it's unclear how to apply this to studies on how FSH-treated silage affects animal performance and meat quality. Therefore, this study aimed to investigate the effects of a standard total mixed ration (TMR) containing anthocyanin-rich black cane silages either with or without dilutions of FSH on animal performance, blood biochemical indices, rumen fermentation, microbial composition, and carcass characteristics in meat goats. Forty healthy crossbred Thai-native Anglo-Nubian male goats (14.42 ± 1.4 kg) were used to compare the feasibility of using anthocyanin-rich black cane silage (ABS) as a functional feed resource as opposed to anthocyanin-rich black cane treated with 0.030% commercial ferrous sulphate heptahydrate silage (ABSF). All goats received a 90-day routine feeding of two isocaloric and isonitrogenous experimental diets: the control group received TMR containing 50% anthocyanin-rich black cane silage (ABS; n = 20), and one group received TMR containing 50% FSH-treating anthocyanin-rich black cane (ABSF; n = 20). As performance indicators, average daily weight gain (ADG) and dry matter intake (DMI) were measured. Samples of meat, blood, and rumen were taken at the end of the experiment. There were no differences in final body weight, ADG, DMI, or ADG/DMI between the two groups. The ABSF group did not differ from the ABS group in terms of rumen pH, but the ABSF had a tendency to lower rumen ammonia N levels, and to higher total volatile fatty acid (VFA) concentrations. Individual VFA concentrations differed, with the ABSF group having more Ruminococcus albus and the ABS group having more methanogenic bacteria. Blood biochemical indices differed, with the ABSF group having lower TBARS concentrations and the ABS group having lower TAC, SOD, CAT, GSH-Px, and GSH-Rx concentrations. In comparison to goat meat from the ABS group, goat meat from the ABSF group contained more intramuscular fat and was more tender. The current results indicate that the feeding of a TMR containing 50% anthocyanin-rich black cane, along with FSH pre-treatment prior to ensiling, reduces oxidative stress and promotes the production of tender meat without